Minat Mahasiswa Menggunakan ChatGPT dalam Pembelajaran Bahasa Arab: Studi pada Mahasiswa PBA UINSI Samarinda - Z, Edy Murdani; Rahman, Nur Fuadi; Yasiron, Aulisa Maulani; Roziqi, M Ainur; Ilmiani, Aulia Mustika (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2025)
This study aims to explore students' interest in using ChatGPT as a learning aid in Arabic language education and analyze the factors influencing their engagement. ChatGPT has significant potential to support language learning; however, its effectiveness depends on students' willingness to use it. This research employs a mixed-methods approach with an explanatory sequential design. Quantitative data were collected through a questionnaire involving 72 Arabic Language Education (PBA) students at UINSI Samarinda. The questionnaire results were analyzed descriptively to determine the level of student interest. Subsequently, semi-structured interviews were conducted with 12 students who participated in the survey to explore the factors influencing their engagement. The findings indicate that students show a high level of interest in using ChatGPT for Arabic language learning, particularly in translation (77.4%), writing (75.5%), and reading comprehension (72.5%). Factors influencing their interest include ease of use, translation accuracy, the ability to generate writing ideas, and the capability to correct language errors. This study confirms that integrating ChatGPT into Arabic language learning can enhance students' interest and overall learning experience.